MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN PERENCANAAN PEMBELAJARAN MELALUI BIMBINGAN BERKELANJUTAN DI SMA NEGERI17 MEDAN - Lukman Pardede (Jurnal Darma Agung, 2019)
This research aims at improving teacher’s competence in arranging the lesson plan through on going guidance. This research was conducted on January of 2019 till March 2019. The subject of the research are 17 teachers that was conducted in SMA N 17 Medan. The method used is Classroom Action Research, refers to the action research model F.X. in which one cycle consists of four (4) components; plan, action, observation and reflection. This research was in two (2) cycles. Data analysis was qualitative method. The qualitative data was taken by observation as long as action intervention by having field notes was done meanwhile quantitative data was taken by comparing the average score of initial assessment result (before giving the treatment) and final assessment (after giving the treatment). Based on he result of Cycle I and II, it can be summarized that there was a significant improvement that can be seen from initial case that 35% of teachers who are not able to make a good lesson plan. The implication of the lesson plan is it should have the components of lesson plan completely because lesson plan is the guidelines in doing the teaching and learning process. The documents of lesson plan should be made in duplicate; one is for school’s files and another one is for teacher as his/her guidelines in having teaching and learning process.